Developing a scheduling framework for line maintenance service checks in airline maintenance, repair and overhaul - Albakkoush, Salah Muftah M. (Cranfield University, 2023)
In today's aviation industry, aircraft must undergo regular maintenance checks, such as transit/ramp-checks, A-checks (line maintenance) and C/D-checks (heavy maintenance), in order for Maintenance Repair and Overhaul (MRO) operators to meet regulatory requirements. These maintenance checks can be planned or unplanned such when an accident occurs, with planned maintenance scheduled according to an aircraft’s flight hours, or flight cycles, or by the calendar. In order for airline MRO (AMRO), and MRO company operators to generate long-term accurate and achievable maintenance schedules which ensure the safety and reliability of aircraft, it is essential that aircraft maintenance is conducted on time and according to relevant regulatory requirements. Effective and efficient scheduling of aircraft maintenance will maximise both the time an aircraft can remain in the air and customer satisfaction. This thesis introduces a novel framework for the scheduling of aircraft maintenance checks, combining mathematical modelling and computer simulation subject to both (i) known constraints such as not permitting the performance of certain tasks simultaneously to avoid adversely affecting safety requirements and avoiding causing injury to personnel, and (ii) maintenance resources such as tools are unexpectedly unavailable. Real data from commercial MROs was used for validation and comparisons; a UK AMRO and a Libyan MRO. Both model and simulated processes and results were subjected to review by five experts in the field, who generally agreed that within its constraints the predictions/simulations were in good agreement with what the experts had found in practice. The scheduling-framework encompasses mathematical and simulation models (in a unified framework). The proposed unified scheduling-framework combining the mathematical and simulation models offers a comprehensive view of the list of tasks to be undertaken and the relationships between them. This approach takes into account the time and efficiency gains that can be achieved when the order of tasks is rearranged, which has traditionally been overlooked in the literature. The model also highlights the benefits of rescheduling in terms of the time needed to complete an activity. Moreover, the simulation model can account for the effect of missing tools, thus providing a clear illustration of the correlation between the number of missing tools and the additional time required to complete the project. Consequently, this approach allows airline MRO operators to evaluate and optimize their project scheduling, thus saving time and money for their organization, while increasing customer satisfaction.
Keywords: Aircraft maintenance scheduling; discrete event simulation; maintenance evaluation and review; maintenance repair and overhaul; project management techniques; scheduling challenges